PENGARUH PEMBELAJARAN KONTEKSTUAL DAN KECERDASAN INTERPERSONAL TERHADAP HASIL BELAJAR IPA SISWA KELAS VI SEKOLAH DASAR - linda sari dewi; Sholeh Hidayat; Dodi Sukmayadi (LPPM Universitas Muhammadiyah Muara Bungo, 2022)
Grade VI students of SDN Tanah Tinggi 4 Tangerang in general, consider Natural Sciences to be an interesting science to learn but the understanding of grade VI students on science learning materials is still not satisfactory, still low results of science learning is very possible because of the use of improper learning methods in the learning process. This study was conducted with the aim to analyze the influence of contextual learning and interpersonal intelligence on the results of science learning of grade VI elementary school students. This study used experiments with 2x2 factorial design. The population in this study was all grade VI students of SDN Tanah Tinggi 4 in the 2020/2021 school year which amounted to 48 students, the research sample was grade VI students of SDN Tanah Tinggi 4 Tangerang City numbering 48 people. Independent variables in this study are contextual learning and interpersonal intelligence, whereas independent variables are the result of studying SCIENCE. Measurement of interpersonal intelligence variables using questionnaires with 30 points of statement, while the measurement of learning results using science study results test in the form of multiple choice consisting of 40 questions. The data analysis uses two-track variance analysis (ANAVA) and continues with the Tukey test. Based on the results of the calculation obtained the results of the study as follows: (1) There are differences in science learning outcomes between students who are studied using contextual learning models with students who are taught using problem-based learning models; (2) There is an influence of contextual learning interaction and interpersonal intelligence on the learning outcomes of grade VI students at SDN Tanah Tinggi 4; (3) There are significant differences in science learning outcomes between students with high interpersonal intelligence who are taught using contextual learning models with students with high interpersonal intelligence who are taught using a problem-based learning model; (4) There are no significant differences in student science learning outcomes that are taught with contextual learning models and have low interpersonal intelligence with science learning outcomes that are taught with problem-based learning models.